Eszkimó asszony fázik - Xantus, János (Hungary : Mafilm, 1983)
It’s hard to believe about Mari, a former runaway girl, with what force she attracts the men in her magic circle. Laci is a renowned pianist who, after colliding with Mari, helps the girl fulfill her ambitions as a singer, completely forgetting everything and especially his own career. He just doesn’t expect Mari to be bound by her strong threads to her husband, János, the deaf-mute zookeeper. And how to handle a love triangle in a reassuring way is unfortunately no recipe for that.
Keywords: Fiction films